INFLUENCE OF ARENA (Arenga pinnata) SUGAR ADDITION WITHDIFFERENT PERCENTES ON THE QUALITY OF CHICKEN MEATFRIED FRUITS: PENGARUH PEMBERIAN GULA AREN (Arenga pinnata) DENGANPERSENTASE YANG BERBEDA TERHADAP KUALITAS DENDENG SAYAT DAGING AYAM - Kemalawaty, Mulla; Irhami; Chairil Anwar; Ika Rezvani Aprita (PT. ROCE WISDOM ACEH, 2025)
Jerky is a traditionally processed meat preservative product. Jerky is a slab-shaped food made from slices or grinds of fresh meat that is seasoned in dry cured meat which has the characteristics of food with low humidity and high protein content. The method used in the research was a completely randomized design (CRD) methods in the same directions with 4 treatment levels (A = 0%, B = 10%, C = 20%, D = 30%) and 5 replications. The results showed that different percentages of addition of palm sugar (0%, 10%, 20% and 30%) had a very significant effect on water content and organoleptic values of colour, taste, aroma and texture and significantly affected the microbial test. The highest water content analysis was found in the handling without the addition of the percentation of palm sugar 0% (13.77%) and the smallest in the handling of 30% (10.48%). The highest total microbial analysis was found in the handling without the addition of 0% palm sugar percentation ( 94.50 cfu / mL) and the smallest at the supplementary of 10% (25.96 cfu / mL) percentages of palm sugar. Jerky in chicken meat with the highest organoleptic quality was acquired in the handling with the supplementary of 30% palm sugar with colour characteristics 2.85; flavour 2,94; smell 2.69; and texture 2.91; at the level of reception rather like.